(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
The study examines relevance of computer in process accounting information in deposit money banks in Nigeria. The purpose of the study is to investigate whether point of sale, internet banking and mobile payment affect processing of accounting information of deposit money banks in Nigeria. The study employed survey research design, using questionnaire as instrument for data collection to assess the suitability of computer methods in processing accounting information. The qualitative data such as point of sales transaction, mobile payment and internet payment were measured using five point likert scale. The study employed correlation technique, ordinary least square regression model and descriptive statistics as a tools for data analyses. Result of the study found that mobile payment, point of sale transaction and internet banking methods significantly affect processing of accounting information of deposit money banks in Nigeria. The study recommended amongst others that deposit money banks in Nigeria should expand and invest more on the services of point of sales transaction so as to enable timely and faithful presentation in the processing in accounting information.